Strategi Digitalisasi Musik Lokal: Studi Peran Media Sosial dalam Popularitas NDX AKA - Amalia Rizky Fatonah; Fitri Nur Ardiantika; Khaylila Safitri; Farel Ziladio Santoso (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the strategy of local music digitalization through the role of social media in enhancing the popularity of the music group NDX AKA. The focus is on three major platforms YouTube, TikTok, and Instagramwhich act as digital ecosystems shaping the existence of hip-hop dangdut music in the new media era. Using a descriptive qualitative approach within the framework of Marshall McLuhan’s media ecology theory, this research draws from an online survey of 95 respondents and observations of NDX AKA’s official social media accounts. Data analysis was conducted to identify media consumption patterns for audience participation, as well as the relationship between musicians and fans in digital spaces. The findings reveal that YouTube serves as the main distribution medium expanding audiences across regions and countries, TikTok acts as a participatory platform driving virality through sound-based challenges, and Instagram functions as an interactive space maintaining fan loyalty. The synergy of these platforms creates a communication ecosystem that strengthens the existence of local music, transforming passive audiences into active communities preserving cultural continuity